Intramolecular cyclopropanation of unsaturated terminal epoxides. - Hodgson, D; Chung, Y; Paris, J (2004)
Efficient lithium amide-induced intramolecular cyclopropanation of bishomoallylic and trishomoallylic epoxides is described. The methodology is used in an asymmetric synthesis of sabina ketone.